THE DEVELOPMENT OF SCIENCE LEARNING MODULE FOR CHILDRENT WITH HEARING IMPAIRMENT - Ahmad Marzuqi; Sihkabuden Sihkabuden (Jurnal Penelitian dan Pengembangan Pendidikan Luar Biasa, 2016)
There are the absence of teaching materials in accordance with the characteristics and conditions of a hearing impairment children in terms of learning, especially science subjects. The characteristics of hearing impairment children is poor in their vocabularies, so that, the teaching materials emphasizing the visual aspect is necessary. This study used a Research and Development (R & D) adapted by the Sugiyono model in order to produce teaching materials in the form of pictorial modules and to test their effectiveness. The result of the research showed that it was a very valid criteria with a score of 97% of the materials experts, 85% of media experts, and 93% of skilled practitioners. The score of the effectiveness of the modules was 75% with the effective criteria.